Malaysian Muslim investors' behaviour towards the blockchain-based Bitcoin cryptocurrency market - Ayedh, A; Echchabi, A; Battour, M; Omar, M (Emerald Group Publishing Ltd, 2024)
Indexed by WOS/Scopus/ERA